ART-RESEARCH IN MEMORY INSTITUTIONS: A BRIEF REVIEW OF THEIR RESOURCES FROM VISUAL-ARTS-RESEARCH PERSPECTIVE - Kumar, Sudhir (International Journal of Research -GRANTHAALAYAH, 2015)
Like the researches in many other fields major part of visual-arts-researches also depends greatly on such memory institutions as libraries and the archives. Besides these there are two other institutions of great importance – the art galleries and the museums, which serve as the most essential place where the visual art researchers may substantiate their research findings. Moreover these are such indispensable the places not only for the commons but also for the art-researchers who want to extend their scholarly contacts and become a part of the broader network of the knowledge and the practices in the area of their research interest. The paper taking a qualitative stance focuses on the availability and accessibility of those resources in these institutions which are especially helpful for the art researchers, and also discusses about what early preparations may be required before an access to these institutions, the ethics and the protocols which should be followed in order to get maximum out of them.